Party fragmentation and campaign spending: A subnational analysis of the German party system. (July 2022) - Jacob, Marc S; Pollex, Jan
Party finance allows elucidating parties' behaviour in differing political and institutional contexts, yet only a few studies investigate expenditure patterns. Given that campaign activities are central for parties to fulfil their core functions in representative democracy, this study seeks to explain why parties invest in electoral campaigns to different degrees. We argue that high party fragmentation reinforces parties' focus on electoral races in election years, a mechanism we refer to as the 'campaign concentration effect'. By contrast, in less fragmented systems, parties invest more in campaigning on a continuous basis. A subnational analysis of the German party system between 2009 and 2017 provides evidence for this effect. Our results imply that growing party fragmentation nurtures parties' efforts to succeed in elections, which is likely to intensify parties' orientation towards short yet capital-intensive campaigns.